Bone Sialoprotein Is Critical for Alveolar Bone Healing in Mice. (February 2023) - Chavez, M.B.; Tan, M. H.; Kolli, T. N.; Zachariadou, C.; Farah, F.; Mohamed, F.F.; Chu, E.Y.; Foster, B.L.
Bone sialoprotein (BSP) is an extracellular matrix (ECM) protein associated with mineralized tissues, particularly bone and cementum. BSP includes functional domains implicated in collagen binding, hydroxyapatite nucleation, and cell signaling, although its function(s) in osteoblast and osteoclast differentiation and function remain incompletely understood. Genetic ablation of BSP in Ibsp knockout ( Ibsp –/– ) mice results in developmental bone mineralization and remodeling defects, with alveolar bone more severely affected than the femurs and tibias of the postcranial skeleton. The role of BSP in alveolar bone healing has not been studied. We hypothesized that BSP ablation would cause defective alveolar bone healing. We employed a maxillary first molar extraction socket healing model in 42-d postnatal Ibsp –/– and wild-type (WT) control mice. Tissues were collected at 0, 7, 14, 21, and 56 d postprocedure (dpp) for analysis by micro–computed tomography (microCT), histology, in situ hybridization (ISH), immunohistochemistry (IHC), and quantitative polymerase chain reaction (qPCR) array. As expected, alveolar bone healing progressed in WT mice with increasing bone volume fraction (BV/TV), bone mineral density (BMD), and tissue mineral density (TMD), transitioning from woven to mature bone from 7 to 56 dpp. Ibsp messenger RNA (mRNA) and BSP protein were strongly expressed during alveolar bone healing in parallel with other osteogenic markers. Compared to WT, Ibsp –/– mice exhibited 50% to 70% reduced BV/TV and BMD at all time points, 7% reduced TMD at 21 dpp, abnormally increased Col1a1 and Alpl mRNA expression, and persistent presence of woven bone and increased bone marrow in healing sockets. qPCR revealed substantially dysregulated gene expression in alveolar bone of Ibsp –/– versus WT mice, with significantly disrupted expression of 45% of tested genes in functional groups, including markers for osteoblasts, osteoclasts, mineralization, ECM, cell signaling, and inflammation. We conclude that BSP is a critical and nonredundant factor for alveolar bone healing, and its absence disrupts multiple major pathways involved in appropriate healing.